Nitrogen fixation of field-inoculated leucaena leucocephala (Lam.) de Wit estimated by the15N and the difference methods - Sanginga, N.; Mulongoy, K.; Ayanaba, A. (1989)
The amount of nitrogen fixed byLeucaena leucocephala (Lam.) de Wit was assessed on an Alfisol at the International Institute of Tropical Agriculture located in southwestern Nigeria. Estimated by the difference method, nitrogen fixation of leucaena inoculated with Rhizobium strain IRc 1045 was 133 kg ha−1 in six months. Inoculation with Rhizobium strain IRc 1050 gave a lower nitrogen fixation of 76 kg ha−1. Fertilization with 40 and 80 kg N ha−1 inhibited nitrogen fixation by 43–76% and 49–71%, respectively. Estimates with the15N dilution method gave nitrogen fixation of 134 kg ha−1 in six months when leucaena was inoculated with Rhizobium strain IRc 1045 and 98 kg ha−1 for leucaena inoculated with Rhizobium strain IRc 1050. This nitrogen fixation represented 34–39% of the plant nitrogen. Inoculated leucaena derived 5–6% of its nitrogen from applied fertilizer and 56–54% from soil.